Ethical Selection and Brain Text: The Development of Ethical Literary Criticism - Yang, Gexin (Archīum Ateneo, 2024)
This essay examines the discursive emergence of ethical literary criticism—a new wave of theory and practice of literary criticism that has developed in the West even as it has also historically thrived in China. It begins with the revival of ethical criticism in the West when American ethical criticism blossomed and advanced new conceptions of reading. The paper then turns “eastward” to China and discusses the historical context in which ethical literary criticism emerged in the country. It surveys the history of importation of Western theories and the resulting inundation of the “theoretical complex” since China’s opening up to the outside world. Finally, the essay focuses on the theoretical elaboration of Nie Zhenzhao to whom is owed the current emergence of ethical literary criticism in China as well as the attention of literary critics and scholars in the West. The paper argues that ethical literary criticism which has grown into a critical movement in China follows this trajectory: from its origins in Ancient Greece, it develops into a trend in the West, and finally gives shape to Nie Zhenzhao’s critical theory, China’s most prominent contribution to the scholarship in the field of ethical literary criticism.